Cinema 4D: Principles of Motion Graphics. - Robinson, Ian (linkedin.com, 2020)
Learn the basics of motion graphics as they apply to Cinema 4D. Discover how to use typography, color, textures, lighting, and transitions and the rich mograph toolset in C4D.